Dampak Multidimensi: Degradasi Lingkungan di Nigeria - Remir Joseph Eklou; I Dewa Ketut Kerta Widana; Suwito (UNIB Press, 2023)
Over the years, the Nigerian government has not given the necessary attention to environmental problems. As a result, environmental resources have suffered the consequences for decades and this remains one of the most complex problems in Nigeria. This study aims to describe the multidimensional impact of environmental degradation in Nigeria. This research was conducted qualitatively using a descriptive research design. The data analysed in this study were obtained from secondary sources in the form of books and scientific journals that were published and were relevant to the topic discussed. This study shows that environmental degradation is a major problem that must be addressed by all levels of Nigerian society. This study presents several recommendations that can be implemented to improve environmental management in Nigeria.